2014
DOI: 10.1371/journal.pbio.1001776
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Helical Motions and Dynamical Asymmetry Modulate Histidine Kinase Autophosphorylation

Abstract: Step-by-step structures of a prototypical E. coli histidine kinase reveal how external stimuli drive helical bending motions to control asymmetric movements of the catalytic domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
171
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(214 citation statements)
references
References 66 publications
(94 reference statements)
26
171
0
3
Order By: Relevance
“…6B). This model is supported by several dimeric HK structures that show that the CA domain can adopt different arrangements with respect to the DHp domain, demonstrating the plasticity of this interface (28,36). Although signaling relies on direct contact between the LOV β-sheet and the DHpL domain for EL346, we envision that, in dimeric HKs, it depends on sensors acting at a distance, modulating the movement of DHp helices from the two protein chains relative to each other.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…6B). This model is supported by several dimeric HK structures that show that the CA domain can adopt different arrangements with respect to the DHp domain, demonstrating the plasticity of this interface (28,36). Although signaling relies on direct contact between the LOV β-sheet and the DHpL domain for EL346, we envision that, in dimeric HKs, it depends on sensors acting at a distance, modulating the movement of DHp helices from the two protein chains relative to each other.…”
Section: Discussionmentioning
confidence: 66%
“…R143A and E246A mutations diminished autokinase activity to levels below those measurable by our assays. Based on the recently reported structures of the autophosphorylating Michaelis complex (20,28), we predict that Glu246 acts as the catalytic base whereas Arg143 helps position it through hydrogen bonding in the active state, making both residues essential for catalysis. Although we cannot precisely determine what specific changes are induced in the DHpL domain without detailed structural information on activated EL346, we can attempt to mimic the active site by superposing the individual DHpL and CA domains from the EL346FL structure onto the autophosphorylationcompetent chain of the Enz chim structure (Fig.…”
Section: Mutations At the Domain Interfaces Affect Signaling And Automentioning
confidence: 98%
“…The activity of histidine kinases is modulated by environmental cues through signal-induced conformational changes (Bhate et al 2015;Mechaly et al 2014;Wang et al 2013). Chemical cross-linking and size-exclusion chromatography were utilised in order to understand the effect of salt stress on Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To probe the contribution of CroS kinase activity toward CroR phosphorylation and cephalosporin resistance, we introduced substitutions at the conserved histidine predicted to be the site of autophosphorylation (H172) or the adjacent acidic residue (D173) which is critical for HK autophosphorylation in other TCS kinases (9,10,45). Phos-tag analysis demonstrated that the CroS H172A variant resulted in some CroR-P that can be detected in a culture without CroRS stimulation, while the CroS D173A variant cannot produce CroR-P even upon stimulation of CroS (Fig.…”
Section: Analysis Of Gene Expression By Quantitative Reverse Transcrimentioning
confidence: 99%